Variation of the transition energies and oscillator strengths for the 3C and 3D lines of the Ne-like ions under plasma environment - Wu, Chensheng; Chen, Shaomin; Chang, T N; Gao, Xiang (Journal of physics. B, Atomic, molecular, and optical physics, 2019)
We present the results of a detailed theoretical study which meets the spatial and temporal criteria of the Debye-Hückel approximation on the variation of the transition energies as well as the oscillator strengths for the 2 p 5 3 d 1 P 1 → 2 p 6 1 S 0 (3C line) and the 2 p 5 3 d 3 D 1 → 2 p 6 1 S 0 (3D line) transitions of the Ne-like ions subject to external plasma. Our study shows that the redshifts of the transition energy follow the general scaling behaviors similar to the ones for the simple H-like and He-like ions. Whereas the oscillator strength for the 3C line decreases, the oscillator strength for the spin-flipped 3D line increases as the strength of the outside plasma increases. As a result, their ratio is amplified subject to outside plasma environment. We further demonstrate that the plasma-induced variation between the relative strength of the 3C and 3D transitions is mainly due to the spin-dependent interactions which dictate the mixing of the 1P1 component in the 3D1 upper state of the 3D transition. In addition, we are able to find that the ratio between the relative oscillator strengths of the 3C and 3D lines in the presence of the plasma to their respective plasma-free values varies as a nearly universal function of [ ( Z − 9.2 ) DZ ] − 1.8 , with Z the nuclear charge and D the Debye length. The results of this study should be of great help in the modelling and diagnostic of astrophysical plasmas as well as laboratory plasmas.